REFINING THE NATIONALISM: CLASSICAL “VERSUS” CONTEMPORARY NATIONALISM - ZulQarnain, Lalu (UI Scholars Hub, 2021)
The resurgence of nationalism in the shape of neo-nationalism and right-wing political parties in Europe and the United States at the end of the twentieth century, followed by similar tendencies in other parts of the world, raises the question of why nationalism is regaining favor again. According to classical nationalism viewpoint, the nationalism term is used to conceptualize the nation-state as the modern state formation that emerged since the 18th century. Though it retains the same ambiguity as classical nationalism, the rise of neo-nationalism in contemporary politics is intriguing and increases interest in studying nationalism, which fails to distinguish between state-nationalism (statist nationalism) and cultural-nationalism (cultural nationalism), each with its own vision and ideals It is also necessary to define the differences between the two types of nationalism, including the debates over Geerzt and Sidel about the future of nationalism in post-colonial countries.